Diabetes and brain health: implications for practice. (10th November 2015) - Dolan, C.; McHugh, J.; Lawlor, B.
Abstract : Background: It is widely accepted that people with mental illness have increased risk of cardiometabolic complications such as obesity and type 2 diabetes mellitus. What is less well known is that individuals with diabetes have an increased risk of brain health complications including depression, cognitive impairment and dementia. These conditions can adversely influence disease self-management and further increase risk of other diabetes complications. Aim: The aim of this paper is to highlight the increased risk of brain health complications in populations with diabetes in order to promote awareness of such complications among healthcare professionals and encourage timely intervention. Methods: An overview of the prevalence and potential mechanisms linking depression and cognitive impairment with diabetes as well as implications for detection, management and brain health protection, based on a narrative review of the literature. Conclusions: Early detection and effective management of depression and cognitive impairment among individuals with diabetes has the potential to minimise adverse health outcomes. In order to promote screening healthcare professionals caring for individuals with diabetes in all settings must be aware of the increased risk of brain health complications in this vulnerable population.